Association between Thyroid Function and Body Mass Index in Normal Population - Suhail Ahmad Gilkar; Shabir ud-din Lone; Javaid Ahmad Khan (Al Ameen Medical College, 2011)
The purpose of this study was to investigate the association between thyroid function and body mass index in a normal population. The study population consisted of a sample of four hundred healthy kashmiri subjects aged 20 - 60 yrs of both sexes. On detailed general physical examination and systematic clinical examination exclusion of the subjects was done with previous or present overt thyroid dysfunction. The study examined the association between serum TSH or T3, T4 and BMI. No association was found between BMI and serum T3 and T4 levels, but there was an association between obesity (BMI >30 kg/m2) and serum TSH levels. Thus results suggest that thyroid function even within normal range could be a factor which determines body weight in a population.